Research Advances in Antitumor Mechanism of Evodiamine - Luning Li; Cunxin Zhang; Chen Huang; Xinchen Tian; Wenxue Sun; Shulong Jiang (Journal of Chemistry)
Evodiamine is a natural alkaloid extracted from Fructus Evodia. This bioactive alkaloid has been reported to have a wide range of biological activities, including anti-injury, antiobesity, vasodilator, and anti-inflammatory effects. In recent years, it has been found that evodiamine has tumor-suppressive effects on a variety of tumors. There is growing evidence that evodiamine can inhibit the rapid proliferation of tumor cells, induce cell cycle arrest at a certain phase, increase the incidence of apoptosis, promote autophagy, inhibit microangiogenesis and migration, and regulate immunotherapy. Evodiamine can inhibit Wnt/β-catenin, mTOR, NF-κB, PI3K/AKT, JAK-STAT, and other signaling pathways in various cancer cells, and it can significantly downregulate the expression of many tumor markers, such as VEGF and COX-2. These facts partially explain the antitumor mechanism of evodiamine. In this article, the antitumor mechanism of evodiamine was reviewed to provide the basis for its clinical application and therapeutic development in the future.